Experimental Study of Two-way Half Slab Precast Concrete using Rextangular Rigid Connection - Djoko Irawan; Ahmad Basshofi Habieb; Data Iranata; Priyo Suprobo; I Gusti Putu Raka (Civil Engineering Dimension, 2024)
A half-slab precast concrete (HSPC) system with precast bottom layers and in-situ cast top layers has been widely applied in various constructions. It generally behaves as a one-way slab due to the absence of positive-flexural reinforcements in the perpendicular direction to the precast component. However, in some cases, the HSPC was also applied in a two-way slab system. Consequently, a particular design and treatment in the connection between precast members was required, so that the bending moment in two orthogonal directions could be accommodated. In the present study, an innovative rectangular rigid connection (RRC) in a two-way HSPC system was investigated through an experimental test. It was found that the RRC-HSPC presented only a 9.13% reduction of the load at the crack, a 16.44% reduction of the ultimate load, and a 6.06% increase of the deflection at the crack when compared to the monolithic one.